2019
DOI: 10.3389/fmicb.2019.02277
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth and Soil Microbial Impacts of Enhancing Licorice With Inoculating Dark Septate Endophytes Under Drought Stress

Abstract: This study mainly aimed to investigate the effects of dark septate endophytes (DSE) (Acrocalymma vagum, Paraboeremia putaminum, and Fusarium acuminatum) on the growth and microbial community composition in the rhizosphere soil of a medicinal plant, licorice (Glycyrrhiza uralensis), grown in the non-sterile soil under drought stress. The results showed that three DSE strains could effectively colonize the plant roots and form a strain-dependent symbiosis with licorice. Although drought stress declined the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 78 publications
5
70
0
Order By: Relevance
“…It was unknown whether DSE-mediated changes in the rhizosphere microbial communities augment drought stress tolerance in licorice. Our previous study showed that DSE inoculation (A. vagum and P. putaminum) improve licorice growth and survival under drought conditions [8]. In the present study, a network structure analysis disclosed that both soil fungal and bacterial networks were characterized by high specialization and modularity.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…It was unknown whether DSE-mediated changes in the rhizosphere microbial communities augment drought stress tolerance in licorice. Our previous study showed that DSE inoculation (A. vagum and P. putaminum) improve licorice growth and survival under drought conditions [8]. In the present study, a network structure analysis disclosed that both soil fungal and bacterial networks were characterized by high specialization and modularity.…”
Section: Discussionmentioning
confidence: 47%
“…Biotic and abiotic stressors alter rhizosphere microbe community structure and may augment or diminish certain microbial populations [32,33]. He et al [8] found that interactions between DSE inoculation and water regime markedly in uenced the soil organic matter content. Compared to the uninoculated condition, A. vagum inoculation under drought conditions increased soil available N and P. In contrast, P. putaminum inoculation decreased soil organic matter and available N relative to the uninoculated condition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations